Stretched up in a tree a knot down in our hands: first record of climbing and defensive habits of Trilepida salgueiroi (Amaral, 1955) (Serpentes, Leptotyphlopidae) - Ugalde, Miguel R. (2025)
Threadsnakes are typical burrowers with specialised diet in social insects. Climbing behaviour has been observed for some of these species although there is no consensus about the nature of such behaviour for fossorial species. In this study we describe the first climbing behaviour for Trilepida salgueiroi in an occasional observation together with the description of the sequence of defensive behaviours displayed during its capture.